Lithium Treatment Is Safe in Children With Intellectual Disability - Yuan, Junying; Song, Juan; Zhu, Dengna; Sun, Erliang; Xia, Lei; Zhang, Xiaoli; Gao, Chao; Agam, Galila; Wang, Xiaoyang; Blomgren, Klas; Zhu, Changlian (Frontiers in Molecular Neuroscience, 2018)
Lithium is a widely used and effective treatment for individuals with psycho-neurological disorders, and it exhibits protective and regenerative properties in multiple brain injury animal models, but the clinical experience in young children is limited due to potential toxicity. As an interim analysis, this paper reports secondary outcome variables, namely, the safety/tolerability profiles of low-dose lithium treatment in children with intellectual disability (ID) and its possible beneficial effects. In a randomized, single-center clinical trial, 124 children with ID were given either oral lithium carbonate 6 mg/kg twice per day or the same dose of calcium carbonate as a placebo (n = 62/group) for 3 months. Primary outcome was the safety of low-dose lithium treatment in children, and all the adverse events were monitored. The secondary outcome was effects on cognition as evaluated by intelligence quotient (IQ), adaptive capacity as assessed by the Infant-Junior Middle School Students Social-Life Abilities Scale (IJMSSSLAS), and overall performance according to the Clinical Global Impression-Improvement (CGI-I) scale. After 3 months of lithium treatment, 13/61 children (21.3%) presented with mild side effects, including 4 (6.6%) with gastrointestinal symptoms, 4 (6.6%) with neurological symptoms, 2 (3.3%) with polyuria, and 3 (4.9%) with other symptoms – one with hyperhidrosis, one with alopecia, and one with drooling. Four children in the lithium group had elevated blood thyroid stimulating hormone, which normalized spontaneously after lithium discontinuation. Both IQ and IJMSSSAS scores increased following 3 months of lithium treatment (F = 11.03, p = 0.002 and F= 7.80, p = 0.007, respectively), but such increases were not seen in the placebo group. CGI-I scores in the lithium group were 1.25 points lower (better) than in the placebo group (F = 82.66, p < 0.001) after 3 months of treatment. In summary, lithium treatment for 3 months had only mild and reversible side effects and had positive effects on cognition and overall performance in children with ID.